2020
DOI: 10.18494/sam.2020.2979
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of Harmful Microorganisms in Hydroponic Cultivation Using an Ultraviolet LED Light Source

Abstract: Hydroponic cultivation is of considerable interest to the production of high-quality green plants. However, establishing the planting operating systems in hydroponic cultivation may result in chronic problems, such as the reproduction of harmful bacteria throughout the circulating culture fluid. Extensive research has been conducted on this type of cultivation using an ultraviolet sterilization system to prevent culture fluid contamination. In this study, the proposed module, using UV-C LEDs that emit waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The relationship between these factors should be investigated in future studies. To further understand the relationship between plant growth and flow patterns in hydroponics, it is essential to study the combined effects of flow patterns with other environmental factors (nutrient solution composition and concentration [8], temperature [28], salinity [11], light intensity and wavelength [34], dissolved oxygen [35], etc.) on the roots and whole plant.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between these factors should be investigated in future studies. To further understand the relationship between plant growth and flow patterns in hydroponics, it is essential to study the combined effects of flow patterns with other environmental factors (nutrient solution composition and concentration [8], temperature [28], salinity [11], light intensity and wavelength [34], dissolved oxygen [35], etc.) on the roots and whole plant.…”
Section: Discussionmentioning
confidence: 99%
“…LEDs are recognized for being environmentally friendly, energy efficient, capable of close-range irradiation, and for generating minimal heat [17]. Research studies have demonstrated that LED light irradiation is highly effective in suppressing the growth of surface microorganisms on fruits and vegetables [18]. Furthermore, it has been observed that it slows down ethylene release and respiration rate, thereby achieving successful post-harvest preservation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported sterilization tests of a homemade sterilizing light source module composed of 40 UVC-LEDs, and it required 30 s to achieve 99% inactivation at an exposure distance of 10 mm [23] . Huang et al demonstrated a flexible sterilization light source consisting of a square array (3 × 3) of UVC-LEDs with an area of 5 × 5 cm 2 , which achieved a 95% sterilization inactivation for Escherichia coli in 60 s [24] . However, the integration level and the LOP of the light source are still not high enough, leading to the requirement of long sterilization time.…”
Section: Introductionmentioning
confidence: 99%